A consciência fonoarticulatória em crianças com desenvolvimento fonológico normal e desviante - Souza, Débora Vidor e (2009)
The articulatory awareness is the part of phonological awareness which is responsible for the distinction of different articulation points of speech sounds. This ability, in addition to improving the perception and production of speech, facilitates learning of an alphabetic writing system. This study aimed to analyze the development of articulatory awareness skills in children with normal phonological development and to verify the articulatory awareness skills of children with speech disorders, comparing them with children with normal phonological development. One hundred and twenty subjects participated of this study. They were students of preschool to first grade of elementary school, and had their articulatory awareness evaluated. Initially, the data of only ninety participants with normal phonological development were analyzed, with the aim of obtaining data about their skills development in articulatory awareness with normal phonological development. Subsequently, data from thirty subjects with speech disorders to thirty subjects with normal phonological development were compared. Based on the analysis of the results, we conclude that the performance in articulatory awareness improves with age and schooling. Female children present better performance than male children. The better is the performance in articulatory gesture perception tasks, the better will be the performance in articulatory gesture production tasks. Children with speech disorders have bigger difficulty in phonological awareness when compared to children with normal phonological development.